Impact of Type of Sport, Gender and Age on Red Blood Cell Deformability of Elite Athletes - Tomschi, Fabian; Bloch, Wilhelm; Grau, Marijke (International Journal of Sports Medicine, 2018)
Our objective was to detect possible differences in red blood cell (RBC) deformability of elite athletes performing different types of sports and being of different age and gender.182 athletes were included in this cross-sectional study. RBC deformability was measured using the laser-assisted optical rotational cell-analyzer. Maximal elongation index (EI max) and shear stress at half-maximum deformation (SS 1/2) were calculated. The ratio SS 1/2 /EI max (EI Ratio) was calculated with low values representing high RBC deformation. Hematocrit (Hct) and mean cellular volume (MCV) were determined in venous blood. Overall RBC deformability did not differ between male and female athletes but, when separated by age of the subjects, RBC deformability increased with age in male but not in female athletes. RBC deformability was lower in Combat sports compared other sport groups. Hct was higher in male compared to female athletes while no difference was observed for MCV. MCV and Hct increased with increasing age. A negative correlation was found between the EI Ratio and MCV and between EI Ratio and Hct. Conclusion: RBC deformability is influenced by age and endurance rate of the sport which suggests that the RBC system may adapt to changing conditions such as adolescence with the onset effects of sex hormones or physical exercise.
Keywords: erythrocyte flexibility; hematocrit; mean cellular volume; training